Rainmaker : superagent Hughes Norton and the money-grab explosion of golf from Tiger Woods to LIV and beyond - Norton, Hughes; Peper, George (Atria Books, 2024)
A rollicking tell-all from golf super-agent, Hughes Norton, detailing everything from his life-changing work with Tiger Woods and Greg Norman to his thoughts on golf's current money-grab era. The ultimate read for fans of Alan Shipnuck, Bob Harig, and Michael Bamberger.